Phenotypic plasticity in the pancreas: new triggers, new players. (December 2017) - Demcollari, Theoni Ingrid; Cujba, Ana-Maria; Sancho, Rocio
Highlights: Cellular interconversions are observed in the adult murine pancreas upon different stimuli. The different cell types of the pancreas are heterogeneous. Ngn3 activation is observed in most of the cellular interconversions within the pancreas. Inter-organ plasticity can be achieved when overexpressing Ngn3, Pdx1 and MafA. Ex vivo models provide a novel platform to explore ways of generating new beta cells. Abstract : The pancreas has a very limited regenerative potential during homeostasis. Despite its quiescent nature, recent in vivo models suggest a certain degree of regeneration and cellular interconversion is possible within the adult pancreas. It has now become evident that cellular plasticity can be observed in essentially all cell types within the pancreas when provided with the right stress stimuli. In this review, we will focus on the latest findings uncovering phenotypic plasticity of different cell types in the pancreas, the molecular mechanisms behind such plasticity and how plasticity associated with pancreatic or non-pancreatic cells could be harnessed in the generation of new insulin-producing beta cells.